Tradisi Muqaddaman di Desa Banjaragung Kecamatan Bangsri Kabupaten Jepara: Sebuah Kajian Living Qur’an - Nur Huda; Ahmad Habiburrohman Aksa; Ahmad Musonnif Alfi; Faridlatus Sya'adah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
The Muqaddaman Tradition in Banjaragung Village, Bangsri District, Jepara Regency: A Study of the Living Qur'anMuqaddaman is an activity of reading the Qur'an which is carried out collectively, in which each individual receives a division of juz from 1 to 30 which is divided randomly according to their respective rations. Muqaddaman is a tradition that has been widely practiced by the Muslim community. This study aims to reveal the aspects of the living Qur’an in the muqaddaman tradition in Banjaragung village through a descriptive-inductive method with Max Weber's theory of social action as the analytical tool. This study seeks to answer how Max Weber's point of view on social action towards the muqaddaman tradition is in Banjaragung village. The results of this study are: First, this tradition is a part of the study of the living Qur’an. Second, based on the type of traditional action, traditional actors want to carry out Islamic religious symbols as traditions that have been carried out by scholars from generation to generation. Third, affective action shows that the perpetrators of the action have an emotional bond with religious leaders and the time of execution (Thursday). Fourth, in term of rational instrumental action, the actors can carry out the tradition rationally and consciously, both from the financial aspect and human resources. Fifth, in term of value rationality, actors want to emulate the behaviour of religious figures, to get used to giving alms, and to instil the value of member solidarity